Valorization of sesame seed coat waste: phenolic composition, antibacterial efficacy, and nanoemulsion encapsulation for food preservation - Khazaal, Salma; Khalil, Mahmoud I.; Osaili, Tareq M.; Albiss, Borhan; Al-Nabulsi, Anas A.; Louka, Nicolas; El Darra, Nada (Frontiers in Nutrition, 2024)
The study highlights the potential of sesame seed coat (SSC), typically discarded during sesame paste productionprocessing, as an impactfula valuable resource for valorization through bioactive compound extraction. It delves into the phenolic composition and antioxidant activity of SSC, alongside assessing its antibacterial properties against foodborne pathogens like Listeria monocytogenes, Escherichia coli O157:H7, and Salmonella Typhimurium. Further, SSC undergoes nanoemulsion coating, analyzed via dynamic light scattering and scanning electron microscopy, to enhance its application as a natural preservative. Specifically, the research focuses on its integration into milk to determine its preservative efficacy. SSC exhibits considerable antioxidant activity and phenolic content, with catechin being the predominant polyphenol. GC-MS analysis identifies seven major compounds, led by oleic acid. Notably, SSC effectively inhibits L. monocytogenes in broth at 100 mg/ml. The application of SSC and its nanoemulsion notably alters bacterial morphology and significantly reduces bacterial counts in milk, emphasizing its potential as an effective natural antibacterial agent. The findings of this study highlight the potential use of SSC as a valuable by-product in the food industry, with significant implications for food safety and preservation.These findings highlight SSC's promise as a valuable byproduct for the food industry, offering substantial implications for food safety and preservation.